Pengaruh DER, IOS, ROE, dan FCF Terhadap DPR Pada Perusahaan Properti dan Real Estate - Nina Purnasari; Chelsy Lorenza; Cindy Cindy; Cynthia Cynthia; Erika Erika; Sherryn Sherryn (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
This study aims to determine the effect of Debt to Equity Ratio, Investment Opportunity Set, Return on Equity and Free Cash Flow on Dividend Payout Ratio. This research is a descriptive research. The sample consisted of 16 Property and Real Estate companies determined by purposive sampling. The study used linear regression analysis as the technique of data analysis. The value of the determinant of Adjusted R Square value was 39,9%. And the remaining 60,1% is explained by other variables not included in the study. The result showed that Debt to Equity Ratio and Free Cash Flow have no effect on Dividend Payout Ratio. Investment Opportunity Set has a positive and significant effect on Dividend Payout Ratio. Return on Equity has a negative and significant effect on Dividend Payout Ratio. Debt to Equity Ratio, Investment Opportunity Set, Return on Equity and Free Cash Flow simultaneously have an effect on Dividend Payout Ratio with a value of Fcount=11,435 > Ftable= 2,53 and a significance 0,000.